ASPECTS OF PATIENT REPORTED OUTCOMES IN RARE DISEASES: A DISCUSSION PAPER. (15th August 2016) - Rüther, Alric; Elstein, Deborah; Wong-Rieger, Durhane; Guyatt, Gordon
Abstract : Objectives: A patient reported outcome (PRO) is "any report of the status of a patient's health condition that comes directly from the patient without interpretation of the patient's response by a clinician or anyone else" (USFDA 2009). PROs are discussed widely, and many regard the patients' perspective on treatment benefit as very valuable. Although many PROs have shown satisfactory measurement properties including reliability, validity, and responsiveness, there is great concern about risk of bias, that is, in clinical trials. Methods: Differences in perspectives of PRO measurement in rare diseases are given arising from methodology, clinical, HTA, and patient advocacy views. Results: PROs are playing an important role in dealing with treatment benefit especially in small sample size as occurring often in rare diseases. Challenges remain especially regarding lack of responsiveness of generic measures, limited capture of all patient relevant aspects, study design and high risk of bias. Conclusions: PROs seem a valuable instrument to detect patient relevant aspects in rare diseases. They should be seen in addition to other approved assessment methods as randomized controlled trials but not as their substitute.